2007
DOI: 10.1016/j.clinph.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

On and Off magnetic auditory evoked responses in early infancy: A possible marker of brain immaturity

Abstract: Measurement of auditory off-responses can improve the assessment of infant neurodevelopment, potentially providing a marker of brain immaturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…The amplitudes of the onsetand offset-responses in infants also seem to be valid markers of brain immaturity. Wakai et al (2007) found that small on-response amplitudes compared to the off-response amplitudes in individual infants were observed in the immature brains. In the future, these types of responses may prove to be useful in assessing the auditory skills very early in life.…”
Section: Event-related Responses Reflecting the Auditory Skillsmentioning
confidence: 94%
“…The amplitudes of the onsetand offset-responses in infants also seem to be valid markers of brain immaturity. Wakai et al (2007) found that small on-response amplitudes compared to the off-response amplitudes in individual infants were observed in the immature brains. In the future, these types of responses may prove to be useful in assessing the auditory skills very early in life.…”
Section: Event-related Responses Reflecting the Auditory Skillsmentioning
confidence: 94%
“…Similarly, during the first 3 postnatal mo, PET activity increases more in the low-expanding (V1) than in the high-expanding (DLPFC) regions (26,38). Activity in the low-expanding auditory cortex in response to sound (39) and medial temporal cortex in response to visually presented faces (40,41) can be detected by PET imaging or scalp recording within the first 2 postnatal mo. In contrast, transcranial magnetic stimulation of the high-expanding motor cortex does not elicit detectable muscle response in humans until 2 y of age (42,43).…”
Section: High-expanding Regions Have Greater Cellular Complexity In Amentioning
confidence: 99%
“…Infant language development has also been studied with ERPs (Buiatti et al, 2009; Cohen et al, 2000; Dehaene-Lambertz et al, 2006). MEG has become a new modality of studying infant brain activity in infant speech perception (Imada et al, 2006; Kujala et al, 2004), sensory perception during sleep (Kakigi et al, 2003), somatosensory development (Pihko et al, 2009), vision (Haddad et al, 2006), and auditory response as an immature brain marker (Wakai et al, 2007). MEG instruments optimized for the pediatric population are beginning to be developed (e.g.…”
Section: Introductionmentioning
confidence: 99%